Factors influencing buying behavior of piracy products and its impact to Malaysian market - Haque, A. K. M. Ahasanul; Khatibi, Ali; Rahman, Sabbir (World Business Institute, 2009)
The primary attempt in this study was to explore the influencing factors of the Malaysian consumers toward the pirated products. To explore these factors, this study has conducted a survey among the Malaysian consumers. The results of the study showed that there is significant relationship between the consumers’ perception and the social influence, personality or believe, pricing and the economy toward the piracy. Results also show that society has strong influence on the consumers’ personality and believes, that leads to grow consumers’ perception. On the other hand, it is revealed that most of the respondents are willing to buy pirated product because cost effective. Since, price plays a key role to convey individuals toward price sensitive, therefore it is important for the marketers or producers to be attentive of pricing. More importantly marketer can decrease the production cost and secondly, they shows intention to reduce their profit margin. To perform all those necessary steps need to set up the price by considering the all income groups. That will help to reducing the consumers’ consumption of pirated goods. Though, there is no doubt about the quality of original products but they should look at the price.